The effect of Psidium guajava hydroalcoholic extract on reducing the expression of Resistin and TNF-α genes in articular chondrocytes of patients with knee osteoarthritis - Wu, Tao (Cellular and Molecular Biology, 2022)
Knee osteoarthritis is the most common joint disease and the most important cause of disability in elderly patients. Due to the side effects of nonsteroidal anti-inflammatory drugs (NSAIDs) in the treatment of osteoarthritis, the use of herbs is recommended as an alternative treatment. The guava fruit can be considered as a natural medicine due to its antioxidant and anti-inflammatory properties. In this study, the effect of Psidium guajava hydroalcoholic extract was considered on reducing the expression of the resistin gene and TNF-α gene in articular chondrocytes of patients with knee osteoarthritis. For this purpose, cartilage chondrocytes of 10 Chinese patients with knee osteoarthritis, who were indicated for arthroplasty, were used for evaluating the effect of guava fruit on the expression of these genes. Articular chondrocytes were cultured under appropriate conditions and their viability was assessed by MTT assay. To increase the level of cytokines, cells were treated with lipopolysaccharide (LPS). They were kept in an incubator with 90% humidity at 37°C for the next steps. Then, the expression of the resistin gene and TNF-α gene was investigated by RNA isolation and cDNA preparation. The results showed that the expression of the resistin gene and TNF-α gene were reduced to 56.59% and 51.86%, respectively, by hydroalcoholic extract of guava fruit. Therefore, according to the results of this study and previous researches, the hydroalcoholic extract of guava fruit (Psidium guajava) can be considered as an effective complementary and alternative treatment for osteoarthritis of the knee.